Parental Support by Highly Educated Offspring: Disparities Across Urban-Rural Contexts and Parental Health Dimensions - Jiaxing Li PhD; Jianyu Chen PhD; Lihua Zhu PhD; Li Luo PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
With rising life expectancy, older adults’ dependency on children for care increases, though the level of support varies based on children’s individual capabilities. In multi-child households, highly educated offspring are often considered to prioritize personal utility, opting to substitute caregiving with financial assistance. However, as parental health declines, their support evolves to stronger reciprocal motivations. Employing a fixed-effects model clustered at the family level and data from the 2018 China Family Panel Studies, this study analyzes intergenerational support within multi-child households, specifically examining how parental health mediates support from highly educated offspring to older adults across urban and rural contexts. Findings highlight the substantial impact of 2 dimensions of parental health on intergenerational support patterns, with highly educated children in urban and rural areas exhibiting different responses. In urban settings, highly educated children tend to provide less caregiving support, increasing their involvement only in response to severe parental depression. In contrast, children of rural areas face greater expectations of reciprocity, offering both financial and caregiving support when their parents’ health deteriorates. This study once again provides empirical support for the health benefits of parental investment in children’s education. Moreover, these findings offer insights for formulating public policies aimed at addressing inequalities in care for older individuals.